2008
DOI: 10.1002/nag.703
|View full text |Cite
|
Sign up to set email alerts
|

A model for pore‐fluid‐sensitive rock behavior using a weathering state parameter

Abstract: SUMMARYChalk and other porous rocks are known to behave differently when saturated with different pore fluids. The behavior of these rocks varies with different pore fluids and additional deformation occurs when the pore fluid composition changes. In this article, we review the evidence that behavior in porous rocks is pore-fluid-dependent, present a constitutive model for pore-fluid-dependent porous rocks, and present a compilation of previously published data to develop quantitative relationships between var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Since the effects of capillarity were deemed to be negligible for the long-term behaviour of calcarenite, chalk and other porous rocks (Ciantia et al, 2014;Papamichos, Brignoli, & Santarelli, 1997;Risnes & Flaageng, 1999;Risnes, Madland, Hole, & Kwabiah, 2005), following Hickman, Gutierrez, De Gennaro, and Delage (2008), the model here illustrated is developed in terms of conventional effective stress that neglects the effects of matrix suction from partial saturation on effective stresses. In the following, the standard apex notation identifying the effective stress has been omitted.…”
Section: General Formulation In Rate Formmentioning
confidence: 99%
“…Since the effects of capillarity were deemed to be negligible for the long-term behaviour of calcarenite, chalk and other porous rocks (Ciantia et al, 2014;Papamichos, Brignoli, & Santarelli, 1997;Risnes & Flaageng, 1999;Risnes, Madland, Hole, & Kwabiah, 2005), following Hickman, Gutierrez, De Gennaro, and Delage (2008), the model here illustrated is developed in terms of conventional effective stress that neglects the effects of matrix suction from partial saturation on effective stresses. In the following, the standard apex notation identifying the effective stress has been omitted.…”
Section: General Formulation In Rate Formmentioning
confidence: 99%
“…It is well known that capillarity effects scarcely affect the mechanical behavior of calcarenites, chalks, and other carbonate porous rocks as the apparent cohesion induced by capillary bridges can be neglected with respect to the natural cementation of the material. Therefore, following , the model here illustrated is developed in terms of conventional effective stresses neglecting the role of matric suction when the material behaves under partially saturated conditions. In other words, in the following, according to the previous assumption σij=σiju*δij where u*={left00Sr<1leftuwSr=1 and u w is the water pressure.…”
Section: The Constitutive Relationshipmentioning
confidence: 99%
“…Studies of chalk reservoirs have shown that replacement of oil with water during enhanced oil recovery by water flooding results in collapse of the overlying rock column (De Gennaro et al 2004;Hickman et al 2008). The collapse is not due to overpressure release since it occurs even when fluid pressure was maintained (De Gennaro et al 2004).…”
Section: Introductionmentioning
confidence: 98%